Clinical and Social Determinants of Quality of Life among People Living with HIV in Jodhpur, Rajasthan: A Cross-Sectional Study using the WHOQOL-HIV BREF. - Mantri, Neha; Goel, Akhil D.; Gupta, Manoj K.; Bohra, Gopal K.; Didel, Siyaram; Rathore, Rashmi; Yadav, Dharamveer; Joshi, Nitin K.; Srinivasan, Srikanth; Kishoria, Naveen; Sharma, Prem P.; Gadepalli, Ravisekhar; et al. (Indian Journal of Community Medicine)
Background: With HIV increasingly managed as a chronic condition under antiretroviral therapy, assessing quality of life (QOL) has become integral to patientcentered care. This study evaluated QOL across multiple domains and identified sociodemographic and clinical determinants among people living with HIV (PLHIV) in western Rajasthan. Methods: A crosssectional study was conducted (March 2024–2025) among PLHIV attending a government ART center in Jodhpur. QOL was measured using the WHOQOLHIV BREF (Hindi version, pretested for reliability). Determinants were examined using descriptive statistics and logistic regression. Results: Among 551 participants (mean age 42.8 ± 12.4 years), the mean overall QOL score was 14.1 ± 2.0. The physical domain scored highest, while social relationships scored lowest. In adjusted models, age >30 years, occupation, and symptomatic HIV status were significant predictors of poor QOL. Spousal absence showed a particularly strong association with diminished independence, underscoring the importance of social support. Viral suppression was modestly linked to better psychological QOL, though the effect size was small. Conclusion: Clinical stage, age, occupation, and spousal support emerged as key determinants of QOL among PLHIV in Jodhpur. These findings highlight the need for integrated interventions that combine medical management with psychosocial counselling and communitybased support to address the multifaceted needs of PLHIV.